The Louisiana Purchase - Fleming, Thomas, 1945- (New Jersey John Wiley & Sons, 2003)
"In 1801, relations between the world's only two republics, the United States and France, were at a low ebb. American merchants had just lost millions of dollars to French privateers in the "Quasi-War" of the late 1790s, and Napoleon was scheming to acquire the Louisiana Territory from Spain and create a "wall of brass" that would halt America's westward expansion. Yet only a few years later, Napoleon agreed to sell Louisiana to the United States for $15 million. How did America manage to double its territory and end French colonial ambitions in the New World - without firing a shot?" "This book by historian Thomas Fleming delivers the answers. Taking us behind the scenes in. Thomas Jefferson's raw "federal village" of Washington, D.C., and inside the duplicitous world of Napoleonic Paris, Fleming shows how Bonaparte haters in Spain, the French army's disastrous failure in Haiti, some wily American negotiating, and Napoleon's resolve to renew his war with "perfidious Albion" led to the momentous French decision to sell Louisiana - and cede 838,000 square miles of land to the United States.
Keywords: Louisiana Purchase -- Geschichte -- Fleming, Thomas, 1945-